I “pericoli” della libertà religiosa al tempo della pandemia: un bilanciamento impossibile? Considerazioni comparate tra Italia e Francia (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Le ragioni di una comparazione - 2. Il caso italiano: una breve cronistoria normativa - 3. Primi appunti giurisprudenziali per un corretto “bilanciamento” - 4. Verso un accomodamento ragionevole - 5. Il paradigma francese e l’opera di bilanciamento del Conseil d’État - 6. Alcune considerazioni in termini di bilanciamento fra libertà di culto e tutela della salute - 7. Minime notazioni di sistema a mo’ di conclusione.The "perils" of religious freedom at the time of the pandemic: an impossible balance? Comparative remarks between Italy and FranceABSTRACT: The essay aims to analyze the measures adopted in the Italian and French legal systems to regulate the exercise of religious freedom during the Covid-19 emergency. The analysis is conducted by observing the various regulatory provisions in the light of the balancing test and the principles of proportionality and reasonableness. This way, the paper will try to verify the overall strength of the constitutional system in times of crisis and the protection of fundamental rights during an emergency.